Measuring The Efficiency of Indonesian Sharia Rural Banks: Two Stage Approach - Rindang Nuri Isnaini Nugrohowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
This paper aims to measure the efficiency level of Sharia Credit Banks in Indonesia over the period of 2012 to 2015. In the first stage, this study uses a Two Stage Approach to measure the level of efficiency with Data Envelopment Analysis (DEA) using the Banxia Frontier Analysis (BFA) software. Then, the second stage involves the analysis of factors that influence the efficiency level of a bank by panel data regression method. On the basis of the test, it is revealed that the Sharia Rural Banks in Indonesia during the study period are not been fully efficient. Some internal factors of the bank, namely BOPO ratios, have a significant adverse impact on the efficiency, while KPPM has a positive and significant influence on the efficiency of BPRS in Indonesia. Meanwhile the total asset, NPF and ROA variables have no significant effect on the efficiency, while the interest rate or BI Rate and inflation have a positive and significant influence on the efficiency of the BPRS.